Rectal bleeding as a symptom of solitary rectal ulcer syndrome mimicking rectal neoplasm on colonoscopy: A case report - Masood Faghih Dinevari; Amirtaher Eftekharsadat; Mahdi Tarverdizadeh; Seyyed Mahdi Rasulimanesh; Ali Riazi; Amirreza Jabbaripour Sarmadian; Samaneh Abbasian (Clinical Case Reports, 2023)
Key Clinical Message Patients complaining of rectal bleeding, constipation, and a suspicious mass in colonoscopy should undergo biopsy. Histological features such as fibromuscular obliteration in the lamina propria favor SRUS, a benign disorder.